PENGARUH PEMBELAJARAN KOOPERATIF DAN MINAT TERHADAP PRESTASI BELAJAR - Narti Narti (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2016)
The purpose of this study is to know how: 1) the influence of cooperative learning to learning achievement in IPS subject of student of SDN I Banjarjo District of Pudak Ponorogo Regency, 2) the influence of interest in learning to learning achievement in IPS subject of student of SDN I Banjarjo District of Pudak Ponorogo Regency, 3) the influence of cooperative learning and interest in learning simultaneously to learning achievement in IPS subject of student of SDN I Banjarjo District of Pudak Ponorogo Regency. This research is a quantitative research by using stratified proportional random sampling with the amount of samples are 30 respondents. Data collection techniques is using questionnaires and documentation. The analysis is using multiple linear regression analysis. Based on the multiple linear regression analysis, obtained the equation: Y = 55,632 + 0,369X1 + 0,162X2. The results showed that there is a significant influence of cooperative learning to learning achievement in IPS subject of student of SDN I Banjarjo District of Pudak Ponorogo Regency because of tstatistic (9,456) > ttable (2,052) or tsig (0,000) < α (0,05). And a significant influence of interest in learning to learning achievement in IPS subject of student of SDN I Banjarjo District of Pudak Ponorogo Regency because of tstatistic (3,018) > ttable (2,052) or tsig (0,005) < α (0,05). In addition, there is significant influence of cooperative learning and interest in learning simultaneously to learning achievement in IPS subject of student of SDN I Banjarjo District of Pudak Ponorogo Regency because of Fstatistic (21,733) > Ftable (3,354) or Fsig (0,000) < α (0,05) with the amount of influence is 79%. While the remaining 21% is influenced by other variables. .